2016
DOI: 10.3329/sja.v13i2.26566
|View full text |Cite
|
Sign up to set email alerts
|

Haemato-biochemical and antioxidant profiling of indigenous cattle of Kashmir

Abstract: ABSTRACT, 3.31±0.07 g dl -1 and 4.95±0.20 gdl -1 respectively that stands higher when compared to the reference values for cattle.Plasma biochemical analytes urea, creatinine, triglycerides, AST and ALT recorded in present study were comparable to the reference values for cattle. All these parameters provide complementary information about the homeostasis of indigenous cattle and indicate its good health status, higher disease resistance and good metabolic defence as compared to exotic or crossbred cattle in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The concentration of different biochemical analytes in the serum (Table 2) was comparable to the values obtained in Indian Zebu cattle (Kalyani et al 2018). Further, the total protein, albumin and globulin values recorded in present study were found to be similar to the earlier reported values in indigenous Kashmir cattle (Pampori et al 2015). Nevertheless, total protein and globulin values recorded in our study were slightly higher than the normal value for cattle.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The concentration of different biochemical analytes in the serum (Table 2) was comparable to the values obtained in Indian Zebu cattle (Kalyani et al 2018). Further, the total protein, albumin and globulin values recorded in present study were found to be similar to the earlier reported values in indigenous Kashmir cattle (Pampori et al 2015). Nevertheless, total protein and globulin values recorded in our study were slightly higher than the normal value for cattle.…”
Section: Resultssupporting
confidence: 88%
“…cattle of hills. The non-descript (local) cattle represent 80% of the total cattle population in India (Pampori et al 2015). Over the centuries these cattle have evolved through natural selection for adoption to adverse climatic conditions, disease resistance etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation